1997
DOI: 10.1088/0953-4075/30/18/011
|View full text |Cite
|
Sign up to set email alerts
|

(e, 2e) collisions on xenon with spin-polarized electrons

Abstract: We present measurements of the (e, 2e) cross sections of xenon for transitions leading to the 5p 3/2 and 5p 1/2 states of the residual ion using an incident polarized electron beam in coplanar asymmetric kinematics and in the intermediate energy regime. The results show that the spin up-down asymmetry for the 5p 3/2 and 5p 1/2 transitions can be understood as an analogue of the so-called fine-structure effect in inelastic scattering. However, our present measurements also point to significant contributions fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…However, neither the use of relativistic target orbitals Granitza et al . 1996), nor the inclusion of continuum spin-orbit interactions (Dorn et al . 1997), provided a significant improvement in the agreement between experiment and theory.…”
Section: (4c) Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, neither the use of relativistic target orbitals Granitza et al . 1996), nor the inclusion of continuum spin-orbit interactions (Dorn et al . 1997), provided a significant improvement in the agreement between experiment and theory.…”
Section: (4c) Results and Discussionmentioning
confidence: 99%
“…So far the investigations for spin-resolved (e, 2e) studies in Xe have concentrated on 147 eV electrons Granitza et al . 1996;Dorn et al . 1997).…”
Section: Spin-resolved Triple Differential Cross Sections Of Xe (4a) mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that certain algebraic relations between the results for p 1/2 and p 3/2 levels, expected from the formal representation of the argument indicated above, were only qualitatively satisfied. Moreover, the DWBA description of these experiments was found to be only moderately successful (Dorn et al 1997). To explain these observations, it has been argued that many-body effects have a significant influence on these outer shell TDCS and asymmetries .…”
Section: (4c) Fine Structure Effectmentioning
confidence: 99%
“…The (e, 2e) fine structure effect has been investigated in detail for the case of the 5p levels of xenon (Guo et al 1996;Hanne 1996;Dorn et al 1997;Mette et al 1998). It was found that certain algebraic relations between the results for p 1/2 and p 3/2 levels, expected from the formal representation of the argument indicated above, were only qualitatively satisfied.…”
Section: (4c) Fine Structure Effectmentioning
confidence: 99%